BONE ALUMINUM AS A BIOLOGICAL MONITORING OF OCCUPATIONAL EXPOSURE TO ALUMINUM - Keyne Christa Monintja; Muhammad Ilyas (The Indonesian Journal of Public Health, 2021)
ABSTRACTThe current proposed biological monitoring of aluminum is based on the analysis of aluminum concentration in blood/serum or in urine, but both considered to be reflective of short-term exposure. Based on its toxic kinetics, aluminum has been demonstrated to be accumulated in the bone. The aim of this study is to find out whether by analyzing bone aluminum, we might have an overview of aluminum accumulation that might cause health problems in the future. This review was conducted through a method of search and selection of articles from Pubmed, Cochrane Library, and Google Scholar databases aimed to answer question rising from the problem statement of this study. The process of searching articles used the keywords “occupational aluminum” OR “bone aluminum” AND “biological monitoring” OR “biomonitoring”. The selection of articles was performed using the defined inclusion and exclusion criteria. Initially, 61 articles were obtained, but after the selection process and hand searching, four articles remained consisting of two case reports and two cross sectional studies. Based on the selected evidence-based resources, bone can be a promising potential biomarker of aluminum, especially for cumulative exposure assessment. The use of in vivo neutron activation analysis (IVNAA) or X-ray fluorescence (XRF) technology for the purpose of noninvasively quantifying aluminum concentration in the bone, is suitable enough to be performed in occupational settings. Keywords: Bone aluminum, occupational exposure, IVNAA, XRF, biomonitoring, biological monitoring